2019
DOI: 10.1186/s12905-019-0861-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of contraceptive use among adolescent girls and young women (AGYW) aged 15 to 24 years in South Africa: results from the 2012 national population-based household survey

Abstract: Background: Despite a variety of contraceptives being available for women in South Africa, a considerable number of adolescent girls and young women still face challenges in using them. This paper examines socio-demographic and behavioral predictors of using contraceptives among adolescent girls and young women (AGYW) aged 15 to 24 years.Methods: A secondary data analysis was conducted based on the 2012 population-based nationally representative multi-stage stratified cluster randomised household survey. Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 25 publications
(29 reference statements)
7
36
1
Order By: Relevance
“…However, in SSA, studies on the predictors of unmet need for contraception among AGYW have been done in specific countries like Ethiopia [13], Senegal [26] and South Africa [17]. There has not been any study that has combined specific high fertility countries in SSA together to understand the reasons for the high unmet need for contraception in AGYW who live in those countries.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…However, in SSA, studies on the predictors of unmet need for contraception among AGYW have been done in specific countries like Ethiopia [13], Senegal [26] and South Africa [17]. There has not been any study that has combined specific high fertility countries in SSA together to understand the reasons for the high unmet need for contraception in AGYW who live in those countries.…”
Section: Plos Onementioning
confidence: 99%
“…Although contraceptives have been considered effective in fertility regulation, their use among AGYW in SSA remains an issue that needs urgent attention [ 12 14 ]. Studies have indicated that despite the desire for AGYW in SSA to use contraceptives, a majority of them have challenges with access to contraceptive services [ 15 17 ]. A useful measure for of the gap between the desire for and access to contraception is the estimation of unmet need for contraception [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vulnerability to HIV acquisition is driven, in part, by power imbalance in relationships with older male partners 19 , 21 , 22 and may be prevented by the administration of PrEP 23 26 . In ongoing efforts to combat the transmission of HIV among AGYW, there is a distinct need for risk assessment tools that capture heterogeneities in AGYW HIV acquisition risk, in addition to the efficient identification of those at high risk of infection 7 , 15 , 20 , 22 , 25 , 26 . Risk assessment tools have successfully predicted HIV acquisition among adult African women 4 , 5 and the development of such prognostic tools for the AGYW population 27 may prove effective in breaking the HIV transmission cycle in South Africa, by directing the administration of PrEP to prevent HIV infection among high-risk AGYW.…”
Section: Discussionmentioning
confidence: 99%
“…In high-prevalence hyper-endemic settings, such as eastern and southern Africa, adolescent girls and young women (AGYW), aged 14–25 years, are particularly vulnerable to HIV acquisition due to power imbalance in sexual relationships 14 19 , particularly those in which HIV is acquired from men over 25 years old 15 , 18 21 , and biological factors (i.e., increased genital inflammation) 18 . Despite their elevated risk of infection, AGYW, particularly those under 18 years, underutilize health services for fear of stigmatization 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation